Laser land leveling in Cambodia and Vietnam - CGIAR Research Program on Rice (2019)
In Vietnam and Cambodia the technology has been extensively demonstrated and services are provided by government institutions. However, there only about 10-20 private sector contract service provisions established in each country. As of 2019, LLL was applied for about 4,000 and 3,500 ha in Vietnam and Cambodia, respectively.